2016
DOI: 10.1080/00268976.2016.1213910
|View full text |Cite
|
Sign up to set email alerts
|

Fractional-charge and fractional-spin errors in range-separated density-functional theory

Abstract: We investigate fractional-charge and fractional-spin errors in range-separated density-functional theory. Specifically, we consider the range-separated hybrid (RSH) method which combines long-range Hartree-Fock (HF) exchange with a short-range semilocal exchange-correlation density functional, and the RSH+MP2 method which adds long-range second-order Møller-Plesset (MP2) correlation. Results on atoms and molecules show that the fractional-charge errors obtained in RSH are much smaller than in the standard Kohn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 67 publications
0
25
0
Order By: Relevance
“…Gradient corrections substantially increased the accuracy of RS MC‐DFT, which also manifested in much lower sensitivity to changes of the range‐separated parameter compared to the local functionals 18,21 . Unfortunately, short‐range GGA exchange‐correlation functionals still suffer from fractional charge and fractional spin errors, although to a lesser extent than the full‐range approximations 39 . Consequently, potential energy surfaces modeled with range‐separated multiconfigurational methods will be inaccurate in the stretched‐bond regions, even if the wavefunction part accounts for the multireference effects.…”
Section: Theory and Implementationsmentioning
confidence: 99%
“…Gradient corrections substantially increased the accuracy of RS MC‐DFT, which also manifested in much lower sensitivity to changes of the range‐separated parameter compared to the local functionals 18,21 . Unfortunately, short‐range GGA exchange‐correlation functionals still suffer from fractional charge and fractional spin errors, although to a lesser extent than the full‐range approximations 39 . Consequently, potential energy surfaces modeled with range‐separated multiconfigurational methods will be inaccurate in the stretched‐bond regions, even if the wavefunction part accounts for the multireference effects.…”
Section: Theory and Implementationsmentioning
confidence: 99%
“…W sr,µ ee = 1 2 w sr,µ ee (r 12 )n 2 (r 1 , r 2 )dr 1 dr 2 , (9) wheren 2 (r 1 , r 2 ) =n(r 1 )n(r 2 ) − δ(r 1 − r 2 )n(r 1 ) is the pair-density operator, written with the density operatorn(r). Equation (6)…”
Section: A Exact Theorymentioning
confidence: 99%
“…As regards the short-range density functional, it is usually decomposed into three contribu-tionsĒ [n] = ē sr,µ,pbe x/c (n(r), ∇n(r)) dr. (15) It has been shown that such semi-local densityfunctional approximations become more accurate as the range of the electron-electron interaction is reduced [2]. Nevertheless, for the values of the range-separation parameter commonly used, the short-range PBE exchange and correlation density functionals still contain substantial self-interaction and static-correlation errors [22]. In lieu of the standard expression of the groundstate energy in the context of RS-DFT using only the long-range electron-electron interaction in the expectation value over the wave function Ψ µ as described by Eq.…”
Section: A Range-separated Density-functional Theorymentioning
confidence: 99%